Carrier drift velocity balance mechanism in Si-based thin film solar cells using graded microcrystalline SiGe absorption layer. (April 2015) - Lee, Ching-Ting; Lu, Kuan-Fu; Tseng, Chun-Yen
Graphical abstract: Highlights: The graded i-SiGe absorption layer was used to balance the carrier drift velocity. The improvement in balance mechanism was studied by the biased quantum efficiency. The carrier recombination loss was reduced due to balanced-carrier drift velocity. Abstract: The basic idea of balancing the carrier drift velocity in the absorption layer was proposed to improve the conversion efficiency of Si-based thin film solar cells. Using the graded microcrystalline i-SiGe absorption layer to modulate the energy band, the driven electric field of holes was increased from 5.92 kV/cm to 7.26 kV/cm, while the driven electric field of electrons was kept at 5.92 kV/cm. Compared with the step i-SiGe absorption layer, the drift velocity ratio of electrons and holes was more balanced. The improvement mechanism of the p-Si/graded-i-SiGe/n-Si solar cells was further analyzed using the measurement of the biased quantum efficiency. Consequently, the short-circuit current density and the associated conversion efficiency of the p-Si/graded-i-SiGe/n-Si solar cells were improved from 21.40 ± 0.47 mA/cm 2 to 26.36 ± 0.56 mA/cm 2 and from 7.43 ± 0.23% to 9.15 ± 0.25%, respectively compared with the p-Si/step-i-SiGe/n-Si solar cells.